Up in the air: the efficacy of weighted gloves in figure skating jumps - Ridge, S. T.; McLean, D.; Bruening, D.; Richards, J. (Sports Biomechanics, 2022)
Successful performance of difficult, multi-revolution jumps is a critical aspect of singles and pairs figure skating. Key determinants of quality jumps include jump height, angular momentum at takeoff (L_BodyTO) and total body moment of inertia (I_Body). The purpose of this study was to determine the effect of weighted gloves on L_BodyTO of figure skating jumps. Kinematic data was collected from thirteen skaters during on-ice testing sessions conducted before and after one week of training with weighted gloves. A one-way repeated measures ANOVA was used to compare metrics from jumps performed pre-training without weights (PreNW), post-training without weights (PostNW) and post-training with weights (PostW). No significant differences were found between kinematics in PreNW and PostNW. Skaters did not pull their arms in as tightly while wearing the weighted gloves (distance from the wrists to the axis of rotation were 13.6% and 12.1% greater in PostW than PreNW and PreW, respectively). A post hoc simulation showed that the added mass affected I_Body in the air. While theoretical evidence supports the use of weighted gloves in figure skating jumps, compensations negated their effectiveness in jumps the skaters could already perform well. Optimal implementation may be when skaters are learning new jumps.